RISK FACTORS FOR END-STAGE RENAL DISEASE IN PATIENTS WITH ARTERIAL HIPERTENSION - Narziyev Shamsidin Saypilloyevich (Scholar Express Journals, 2023)
These risk factors for terminal renal failure in patients suffering from hypertension were studied. In patients before the development of end-stage renal failure, the content of urea and creatinine was studied. When examining the outpatient card of patients before the development of terminal renal failure, it was found that in some patients, starting from 7 years after suffering hypertension, an increase in the content of urea from 9.2 to 12.1 mmol / l and creatinine from 0.189-0.237 mmol / l in the blood was observed sick.
Keywords: Hypertension; end-stage renal failure